2020
DOI: 10.1108/ils-04-2020-0096
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining rich dialogic interactions in the transition to synchronous online learning

Abstract: Purpose The authors present the first author’s recent experience as a design case, capturing approach and principles to transitioning a course from in-person to remote modality while maintaining its collaborative, synchronous and dialogic nature. Design/methodology/approach A mathematical content course for preservice teachers at a mid-Western university was used as a site for this case study. Data include video recordings of synchronous online sessions, students’ written work and their reflections. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…In our study, it became evident that participants were attempting to optimize the affordances of the communication medium in other ways such as hosting discussions, whiteboarding, and screen sharing with students. This finding aligns with previous research which has shown that discussion-based synchronous sessions have been beneficial to building classroom community in online courses (Brown & Eaton, 2020;Jung & Brady, 2020).…”
Section: Experiences Using Synchronous Video-based Communication In O...supporting
confidence: 92%
“…In our study, it became evident that participants were attempting to optimize the affordances of the communication medium in other ways such as hosting discussions, whiteboarding, and screen sharing with students. This finding aligns with previous research which has shown that discussion-based synchronous sessions have been beneficial to building classroom community in online courses (Brown & Eaton, 2020;Jung & Brady, 2020).…”
Section: Experiences Using Synchronous Video-based Communication In O...supporting
confidence: 92%
“…The papers coded under this theme include those concerned with the use of technology to promote delivery and communication in the online classroom. This was frequently commented on in papers, with some reporting that technology was key to establishing social norms in online classroom settings (Jung and Brady, 2020). However, the time span of this review, limits some of the usefulness of these findings as newer technological advances such as Whatsapp were not featured.…”
Section: Resultsmentioning
confidence: 99%
“…Selain itu, peserta didik akan mengalami peningkatan kemampuan dalam menganalisis materi pembelajarannya (Wahyuni et al, 2019). Selanjutnya, pembelajaran tatap muka atau synchronous dapat dilakukan secara tatap maya atau dikenal juga dengan synchronous online (Jung & Brady, 2020). Hal ini sesuai dengan aturan yang dikeluarkan oleh pemerintah bahwa pembelajaran tatap muka diganti dengan pembelajaran secara daring.…”
Section: Pendahuluanunclassified